Single-cell and spatial transcriptomics reveal a stress-induced EMT-like epithelial subset driving immune activation in silica-injured lung - Wang, Tao; Hao, Jianfeng; Li, Bing; Hyraht, Ahjol; Wang, Jialing; Xia, Henglei; Wu, Qingbin; Gao, Wei; Chen, Congxia; Yu, Chuanqing; Gong, Xiuqun; Li, Ting; et al. (Frontiers in Immunology, 2025)
The mechanism that lung epithelial cells regulate immune responses during chronic injury still remains unclear. Here, we combined single-cell RNA sequencing with spatial transcriptomics to track epithelial dynamics in silica (SiO2)-exposed mouse lungs. By day 56, SiO2 induced significant epithelial proliferation, followed with a distinct C0 subset emerging as the dominant population. C0 cells co-expressed surfactant genes (Sftpc, Scgb3a2), mesenchymal markers (Vim, Mmp12), and pro-inflammatory cytokines (Ccl6, S100a8/a9), reflecting a hybrid phenotype. Spatial and cell-cell interaction analyses showed C0 cells engaging macrophages and neutrophils through SPP1-CD44, APP-CD74, and GRN-MARCO signaling, driving immune recruitment and activation. Pseudotime and CytoTRACE analyses indicated that C0 cells represent a late-stage, low-stemness state with epithelial-mesenchymal transition (EMT)-like features. Taken together, these findings reveal a novel, stress-induced epithelial subset that amplifies immune crosstalk and tissue remodeling, offering new perspectives on silica-induced lung injury.